The predictive value of preoperative luteinizing hormone to follicle stimulating hormone ratio for ovulation abnormalities recovery after laparoscopic sleeve gastrectomy: A prospective cohort study - Liu, Fashun; Li, Yue; Ye, Zhenxiong; Jiang, Xiaohua; Liu, Ruichen; Li, Zhen; Ma, Chiye (Frontiers in Endocrinology, 2023)
Background: Obesity-related ovulation abnormalities (OA) affect fertility. LSG is the most frequent bariatric operation. However, no research has identified a reliable indicator for predicting OA recovery after LSG. The purpose of this research was to examine the prognostic usefulness of preoperative the luteinizing hormone (LH) to follicle-stimulating hormone (FSH) ratio (LFR). Methods: Our department conducted a prospective study from 2016 to 2021. Venous blood was typically tested 3 days before surgery to get the preoperative LFR. Descriptive data, preoperative and postoperative variables were also collected. Binary logistic regression related preoperative LFR with OA recovery. The receiver operating characteristic (ROC) curve evulated preoperative LFR's predictive capability. Results: A total of 157 women with a complete follow-up of one year were included. LFR was the only factor linked with OA (P < 0.001). AUC (area under the ROC curve) = 0.915, cutoff = 1.782, sensitivity = 0.93, and specificity = 0.82. Conclusion: Overall, LSG has a favorable surgical result, with a %TWL of 66.082 ± 12.012 at 12 months postoperatively. Preoperative sexual hormone levels, as expressed by LFR, has the potential to predict the fate of OA following LSG at one year post-operatively.